2023
DOI: 10.4240/wjgs.v15.i4.544
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for recurrent hepatocellular carcinoma: Current status and challenges

Abstract: Primary liver cancer is the sixth most commonly diagnosed cancer and was the third leading cause of cancer deaths worldwide in 2020. It includes hepatocellular carcinoma (HCC) (representing 75%-85% of cases), intrahepatic cholangiocarcinoma (representing 10%-15% of cases), and other rare types. The survival rate of patients with HCC has risen with improved surgical technology and perioperative management in recent years; however, high tumor recurrence rates continue to limit long-term survival, even after radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…This raises a significant need to improve models for the early detection of patients at risk of recurrence. Many factors have been identified in predicting risk of recurrence of HCC[ 2 ] and this editorial explores the promising avenue in the quest for precision medicine[ 1 ] the development of a machine learning model as highlighted by the authors aimed at predicting early recurrence after surgical intervention[ 7 ]. The advent of machine learning provides a unique opportunity to harness vast datasets, identifying subtle patterns and factors that elude conventional prognostic methods[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This raises a significant need to improve models for the early detection of patients at risk of recurrence. Many factors have been identified in predicting risk of recurrence of HCC[ 2 ] and this editorial explores the promising avenue in the quest for precision medicine[ 1 ] the development of a machine learning model as highlighted by the authors aimed at predicting early recurrence after surgical intervention[ 7 ]. The advent of machine learning provides a unique opportunity to harness vast datasets, identifying subtle patterns and factors that elude conventional prognostic methods[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatectomy, as the first line of treatment for HCC in patients with preserved liver function, is the best treatment method compared to local ablation and chemoembolization [ 9 12 ]. However, the survival rate of these patients is still short and unsatisfactory due to the high recurrence of HCC after hepatectomy [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, traditional treatments for HCC patients showed poor clinical effects 5 . VI is a significant factor affecting prognosis in HCC 6 . Another study also reported that patients with VI, compared to those without evidence of VI, showed a shorter median survival 7 .…”
Section: Introductionmentioning
confidence: 99%